Orexin 1 receptors in the anterior cingulate and orbitofrontal cortex regulate cost and benefit decision-making - Karimi, Sara; Hamidi, Gholamali; Fatahi, Zahra; Haghparast, Abbas (Progress in neuro-psychopharmacology & biological psychiatry, 2019)
Orexin neurons are discretely localized within the lateral hypothalamus and have widespread projections into all areas of the brain. In addition, several lines of evidence specify that orexins may also participate in the regulation of a variety of affective and cognitive processes. The Orexin-1 receptor (OX1r) is distributed extensively throughout the prefrontal cortex (PFC). Delay-based decision- making is mediated largely by the orbitofrontal cortex (OFC) while effort- based decision-making is controlled by the anterior cingulated cortex (ACC). Hence, in the present study, a series of experiments were conducted to clarify the role of OX1r in the mPFC (ACC and/or OFC) in cost and benefit decision-making. The rats were trained in a delay and/or effort-based form of cost-benefit T-maze decision-making task. Two goal arms were different in the amount of accessible reward and cost. Before surgery, all animals were selecting the high reward arm and pay the cost on almost every trial. During the test days, the rats received local injections of either DMSO 20% /0.5 μl, as a vehicle, or SB334867 (3, 30 and 300 nM/0.5 μl), as a selective OX1r antagonist, within the ACC and/or OFC. The results of this study showed that the bilateral microinjection of SB334867 into ACC and/or OFC changed the preference to a low reward arm with no cost, indicating the role of OX1 receptors in cost and benefit decision- making. From these results, it can be implied that OX1 receptors in the mPFC play a crucial role for allowing the animal to evaluate and pay the cost to acquire greater rewards. •Blockade of ACC OX1r significantly decreased tending to high reward in effort-based decision-making.•Blockade of OFC OX1r significantly decreased tending to high reward in delay-based decision-making.•Administration of SB334867 in the OFC increased decision-making time